Cytotoxic effect of PEI-coated magnetic nanoparticles on the regulation of cellular focal adhesions and actin stress fibres - Narayanasamy, Kaarjel K.; Price, Joshua C.; Merkhan, Marwan; Elttayef, Ajile; Dobson, Jon; Telling, Neil D. (Materialia, 2020)
The biocompatibility of surface-coated magnetic nanoparticles (MNPs) is key to their successful use in biomedical applications. Polyethyleneimine-coated MNPs (MNP-PEIs) provide improved in vitro nucleic acid transfection efficiency and are safer compared to conventional chemicals. Commercial cell toxicity assays are useful for end-point and high-throughput screening, however, they only reports cells that have undergone an extreme toxic response leading to cell death. Cell toxicity is a complex process which can be expressed in many forms, through morphological, metabolic, and epigenetic changes. This study explores the effect of magnetic transfection with MNP-PEIs and an external magnetic field on cell toxicity, by studying particle internalization, changes in cellular morphology, and cell adhesion. We show that MNP-PEIs induce cell stress through a dose-dependent increase in cell adhesion via the overexpression of vinculin and formation of actin stress fibres. While the presence of PEI was the main contributor to increased cell stress, free PEI polyplexes induced higher toxicity compared to PEI bound to MNPs. MNPs without PEI coating however did not adversely affect cells, suggesting a chemical effect instead of a mechanical one. In addition, genes identified as being associated with actin fibre regulation and cell adhesion showed significant increases in expression from MNP-PEI internalization. From these results, we identify anomalous cell behaviour, morphology, and gene expression after interaction with MNP-PEIs, as well as a safe dosage to reduce acute cell toxicity.
Online verfügbar: 11. August 2020
Gesehen am 22.12.2025